Analysis of Clinical Research Trends for Thread Embedding Acupuncture of Cervical Radiculopathy - Eun Sil Heo; Hyun-Jong Lee; Jung Hee Lee; Sang Ha Woo; Yun Kyu Lee; Seong Hun Choi; Jae Soo Kim (MEDrang Inc., 2022)
In this study, the evidence of thread embedding acupuncture (TEA) in treating cervical radiculopathy in randomized controlled trials was investigated. We searched 16 databases up to August 22, 2022. Of the 2,644 studies retrieved, 22 randomized controlled trials (2,483 participants) were selected. Quality assessments were performed using Cochrane's risk-of-bias tool and RevMan 5.4 software. Outcome measures in the included studies typically showed TEA had a significant therapeutic effect compared with simple acupuncture and other remedies, and TEA was better than sham TEA. Catgut and polydioxanone had no difference in effectiveness, however, catgut was considered to be less safe. TEA was shown to be more therapeutic when inserted deeper into the skin. Ultrasound guided TEA was more effective and safer than conventional TEA, and using a flat blade needle was better than conventional needles for TEA. No serious adverse events were reported from using TEA, and only a few mild side effects were observed. However, the limited number and heterogeneity of the included studies, together with the unclear methodological quality, indicate that higher-quality studies need to be conducted to determine the effectiveness and safety of TEA for cervical radiculopathy.